Evaluation of Different Mutants Against Insect and Mite Pests With Natural Enemies in Coastal Jute Ecosystem - Khan, MMH (Journal of the Asiatic Society of Bangladesh, Science, 2018)
Jute is a rapid growing agricultural fiber crop and renewable source of biomass. The study was conducted to evaluate different jute mutants against insect and mite pests with associated natural enemies. Results revealed that 8 insect and mite pests and 8 natural enemies were recorded from coastal jute ecosystem. Jute hairy caterpillar and yellow mite were found to be the most damaging pests in jute field. Significantly the lowest per cent plant infestation per 5 rows was recorded in mutant BJC-214 (14.37) followed by BJC-7370 (14.81) and the highest per cent plant infestation (30.77) was found in mutant VM-1. Significantly the lowest per cent leaf infestation was in mutant HC-3 (25.40) followed by HC-95 (31.08) while the highest per cent leaf infestation per plant was recorded in mutant BJC-83 (46.30). In case of leaf area damage, the lowest per cent was observed in mutant HC-3 (9) followed by CVL-1 (10) and the highest was in mutant CVE-3 (45) followed by mutant 0-72 (30). Among different mutants, HC-3, CVL-1 and BJC-214 were found to be less infested by jute hairy caterpillar and these mutants could be used for multilocational trial for final recommendation as the tolerant mutants. Asiat. Soc. Bangladesh, Sci. 44(1): 23-33, June 2018